GRAMMATICAL COHESIVE FEATURES IN INDONESIAN EFL STUDENTS’ ARGUMENTATIVE ESSAYS - Dian Agustina Purwanto Wakerkwa (PT Akselerasi Karya Mandiri, 2024)
This study investigates the use of grammatical cohesion in the argumentative essays written by Indonesian English as a Foreign Language students. Cohesion, a crucial component of textual coherence, ensures that discourse elements are logically connected, thereby enhancing the readability and comprehensibility of written texts. By analyzing a corpus of 7 students’ essays, this research identifies the frequency and types of cohesive devices employed while at the same time observing the coherence built through the use of these devices using Halliday and Hasan’s (1976) cohesion conceptual framework. The findings demonstrate prevalent patterns where the reference devices were used more frequently than conjunctive devices. It suggests that the lack of understanding of grammatical cohesion can lead to potential challenges for learners in utilizing cohesive mechanisms effectively.